The prognosis difference between elderly and younger patients with adrenocortical carcinoma - He, Shengyin; Huang, Xuemei; Zhao, Pan; Zhang, Peng (Frontiers in Genetics, 2023)
Background and aim: Adrenocortical carcinoma (ACC) is uncommon in the elderly. This study aimed to compare the surgical prognosis and survival between senior and younger patients. We also explored the factors that were independently related to the survival of elderly patients. Methods: We identified ACC patients between 2010 and 2019 in the Surveillance, Epidemiology, and End Results (SEER) database and applied Kaplan-Meier curves to evaluate the overall survival (OS) and cancer-specific survival (CSS) with log-rank tests. We also used Cox regression analysis to estimate the OS and CSS. The Fine and Gray model with the Gray test was used to measure the cumulative incidence function (CIF) of CSS and other mortality causes of patients in a competing-risks setting. Results: Of 876 patients, 44.06% were elderly. A lower proportion of elderly patients underwent surgery, regional lymph node surgery, and chemotherapy than young patients. Elderly patients also had inferior OS and CSS than younger patients. The 1- and 5-year OS of elderly patients who underwent surgery were 68% [95% confidence interval (CI): 62-74%] and 30% (95% CI: 24-38%), and the 1- and 5-year CSS were 73% (95% CI: 67-80%) and 40% (95% CI: 32-47%). The factors independently related to worsened survival included age ≥ 60 [Hazard Ratio (HR): 1.47 (1.24-1.75)], metastatic disease [HR: 1.90 (1.49-2.51)], higher grade [HR: 1.94 (1.08-3.46)] and Network for the Study of Adrenal Tumors (ENSAT) stage [HR: 1.99 (1.48-2.66)]. Conclusions: Younger ACC patients had better survival than the elderly. Factors independently related to worsened survival in elderly patients included age ≥ 60, metastatic disease, higher grade, and European ENSAT stage.